Psychology - Wade, Carole; Tavris, Carol (New York : Harper & Row Publishers, 1987)
The sixth edition of this acclaimed introductory psychology text. It integrates perspectives on gender, culture and ethnicity, and features quick quizzes and new review summary tables that summarize
includes bibliography and index.
Keywords: psychology